Inhibition of hepatocyte nuclear factor 4 confers imidacloprid resistance in Nilaparvata lugens via the activation of cytochrome P450 and UDP-glycosyltransferase genes. (January 2021) - Cheng, Yibei; Li, Yimin; Li, Wenru; Song, Yuanyuan; Zeng, Rensen; Lu, Kai
Abstract: Increasing evidence indicates that insect resistance to synthesized insecticides is regulated by the nuclear receptors. However, the underlying mechanisms of this regulation are not clear. Here, we demonstrate that inhibition of hepatocyte nuclear factor 4 (HNF4) confers imidacloprid resistance in the brown planthopper (BPH) Nilaparvata lugens by regulating cytochrome P450 and UDP-glycosyltransferase (UGT) genes. An imidacloprid-resistant strain (Res) exhibited a 251.69-fold resistance to imidacloprid in comparison to the susceptible counterpart (Sus) was obtained by successive selection with imidacloprid. The expression level of HNF4 in the Res strain was lower than that in Sus, and knockdown of HNF4 by RNA interference significantly enhanced the resistance of BPH to imidacloprid. Comparative transcriptomic analysis identified 1400 differentially expressed genes (DEGs) in the HNF4 -silenced BPHs compared to controls. Functional enrichment analysis showed that cytochrome P450- and UGT-mediated metabolic detoxification pathways were enriched by the up-regulated DEGs after HNF4 knockdown. Among of them, UGT-1-7, UGT-2B10 and CYP6ER1 were found to be over-expressed in the Res strain, and knockdown of either gene significantly decreased the resistance of BPH to imidacloprid. This study increases our understanding of molecular mechanisms involved in the regulation of insecticide resistance and also provides potential targets for pest management. Graphical abstract: Image 1 Highlights: Hepatocyte nuclear factor 4 (HNF4) negatively regulates imidacloprid resistance. Transcriptomic analysis identified seven metabolic resistance pathways after HNF4 silencing. Inhibition of HNF4 activates P450s and UDP-glycosyltransferases (UGTs). P450s and UGTs are involved in the imidacloprid resistance.